2022
DOI: 10.3389/fneur.2022.882334
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of the Diffusion-Weighted Imaging Method Used in Association With the Apparent Diffusion Coefficient for Differentiating Between Primary Central Nervous System Lymphoma and High-Grade Glioma: Systematic Review and Meta-Analysis

Abstract: BackgroundIt is difficult to differentiate between a few primary central nervous system lymphoma (PCNSL) and high-grade glioma (HGG) using conventional magnetic resonance imaging techniques. The purpose of this study is to explore whether diffusion-weighted imaging (DWI) can be effectively used to differentiate between these two types of tumors by analyzing the apparent diffusion coefficient (ADC).Research Design and MethodsData presented in Pubmed, Embase, Web of Science, Cochrane Library, China National Know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…For instance, a study used DWI in association with ADC to differentiate between CNS gliomas and PCNSLs, but the findings indicated a slightly lower diagnostic performance, with a SEN of 82% (95% CI 0.75-0.88) and a SPE of 87% (95% CI 0.84-0.90) ( 27 ). Similarly, in another study, the diagnostic efficacy of DWI was investigated for the same discrimination task, but it also exhibited lower performance, with SEN at 82% (95% CI 0.70-0.90) and SPE at 84% (95% CI 0.75-0.90) ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study used DWI in association with ADC to differentiate between CNS gliomas and PCNSLs, but the findings indicated a slightly lower diagnostic performance, with a SEN of 82% (95% CI 0.75-0.88) and a SPE of 87% (95% CI 0.84-0.90) ( 27 ). Similarly, in another study, the diagnostic efficacy of DWI was investigated for the same discrimination task, but it also exhibited lower performance, with SEN at 82% (95% CI 0.70-0.90) and SPE at 84% (95% CI 0.75-0.90) ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…MRS plays a crucial role in the evaluation of PCNSL. Elevated choline peak, decreased N-acetylaspartic acid, and a towering lipid peak are commonly observed[ 12 ]. The towering lipid peak is highly specific for the diagnosis of PCNSL, attributed to the accelerated turnover of lymphocytes and macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Computed Tomography (CT), the primary method for imaging of craniocerebral diseases is craniocerebral Magnetic Resonance Imaging (MRI), which has the ability to diagnose as well as differentially diagnose intracranial diseases (23)(24)(25). For example, a meta-analysis of 18 studies by Du et al suggested that DWI could differentiate between PCNSL and HGG with an AUC of 0.90 (26). Another meta-analysis of 10 articles by You et al suggested that arterial spin labeling could differentiate between PCNSL and HGG with an AUC of PET / CT imaging is an advanced imaging technology that can simultaneously capture the cellular, molecular level images and anatomical structures through an image-fusion technology.…”
Section: Discussionmentioning
confidence: 99%